2019
DOI: 10.1371/journal.pone.0211326
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced adherence counselling and viral load suppression in HIV seropositive patients with an initial high viral load in Harare, Zimbabwe: Operational issues

Abstract: BackgroundIn people living with HIV (PLHIV) who are on anti-retroviral therapy (ART), it is essential to identify persons with high blood viral loads (VLs) (≥1000 copies/ml), provide enhanced adherence counselling (EAC) for 3 months and assess for VL suppression (<1000 copies/ml).ObjectiveOur study objectives were to determine the proportion who had a high viral load in those people who underwent viral load testing between 1 August 2016–31 July 2017 at Wilkins Hospital, Harare, Zimbabwe. Of those with high vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
104
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(131 citation statements)
references
References 8 publications
18
104
9
Order By: Relevance
“…Fourth, risk factors for virologic failure in both cohorts were advanced HIV-related disease and/or immunosuppression. These findings are in line with previous reports [ 29 , 30 , 31 ], although associations between advanced HIV disease and virologic failure are not always consistent [ 32 , 33 ]. Being married or widowed offered protection in the 12-month cohort against virologic failure and this is possibly due to the supportive efforts of spouses/families in ensuring adherence to treatment and compliance with follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Fourth, risk factors for virologic failure in both cohorts were advanced HIV-related disease and/or immunosuppression. These findings are in line with previous reports [ 29 , 30 , 31 ], although associations between advanced HIV disease and virologic failure are not always consistent [ 32 , 33 ]. Being married or widowed offered protection in the 12-month cohort against virologic failure and this is possibly due to the supportive efforts of spouses/families in ensuring adherence to treatment and compliance with follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…In one study from Uganda, in which only 25% of patients resuppressed, over half of patients received their first session more than six months after an elevated viral load was first detected Longer time on first‐line ART has been found to be associated with a lower likelihood of resuppression ; this is likely related to the observation that resuppression rates are lower in patients on first‐line ART in whom antiretroviral drug resistance mutations were subsequently detected . This review found higher rates of resuppression among patients on second‐line ART, consistent with the finding from Zimbabwe that being on second‐line ART at the time of initial high viral load test was associated with a higher probability of viral resuppression . The overall resuppression estimate from this meta‐analysis should therefore be considered a conservative estimate of the proportion of patients who could resuppress following adequate enhanced adherence support, given that the quality and approach to providing enhanced adherence support varied across studies and was not consistently reported.…”
Section: Discussionsupporting
confidence: 74%
“…One study, from eSwathini, found that in logistic regression the odds of resuppression increased when additional enhanced adherence counselling sessions was provided, compared to no intervention . A study from Zimbabwe found that patients undergoing three sessions of enhanced adherence counselling were more likely to resuppress compared to non‐attendance to enhanced counselling (relative risk of resuppression 2.8, 95% CI 1.8 to 4.2) . A study from South Africa found only a small benefit to EAC in terms of viral suppression within three months (8.1% increase compared to those not receiving EAC in adjusted analysis), and this difference was not sustained over 12 months .…”
Section: Discussionmentioning
confidence: 99%
“…An individual who had greater than or equal to 5,000 copies/ml initial viral load levels were less likely to develop viral load suppression. is finding is supported by previous studies which showed that initial viral load levels may be a good determinant of viral load suppression in patients with high viral load [16,28]. e major strength of the study was inclusion of all public hospitals in North Wollo Zone and inclusion of all high viral load patients for the last 2 years.…”
Section: Discussionsupporting
confidence: 69%
“…is re-suppression rate is near to the WHO target (70%) [3]. But it is much higher than the viral suppression rates reported in Zimbabwe [16] and Uganda [11]. Most importantly, the current finding support WHO recommendations that suspected virologic failure (viral load count>1,000 copies/µl at the first test) should be addressed by enhanced adherence counseling as well as repeat measurement before consideration of treatment switch to a second-line drug [3,10].…”
Section: Discussionmentioning
confidence: 88%